Quantitative 3D Micro-CT Imaging of Human Lung Tissue - Kampschulte, M.; Schneider, C. R.; Litzlbauer, H. D.; Tscholl, D.; Schneider, C.; Zeiner, C.; Krombach, G. A.; Ritman, E. L.; Bohle, R. M.; Langheinrich, A. C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To assess the feasibility of micro-CT for obtaining quantitative volumetric and morphologic information of changes in soft tissue, respiratory tracts and vascularization in fibrotic, emphysematous and non-diseased human lung specimens.Materials and Methods: Specimens from autopsy or lung explantation with lung fibrosis of UIP pattern (n = 22) or centrilobular emphysema (n = 10) were scanned by micro-CT and compared to controls (n = 22). Imaging was performed subsequent to intravascular contrast enhancement for the assessment of the vascular volume fraction. The soft tissue and air fraction were quantified after the fixation of ventilated lungs followed by tissue contrast enhancement using osmium. Aiming an artifact-free 3 D reconstruction of lung acini, synchrotron-based micro-CT scans of specimens with emphysema (n = 5) and non-diseased tissue (n = 6) was performed. Micro-CT imaging was complemented by histology for the demonstration of comparable findings.Results: Quantitative analysis showed a significant increase of the soft tissue fraction, equivalent to a decrease of the air fraction in fibrotic lungs compared to controls (p < 0.001) and a significant reduction of the vascular volume fraction compared to controls (p < 0.02). Specimens with emphysema demonstrated a significant increase of the air fraction with a decrease in soft tissue compared to controls (p < 0.001). 3 D reconstructions of lung acini worked successfully in non-diseased tissue but failed in fibrotic and emphysematous lungs.Conclusion: Our findings indicate micro-CT’s technical feasibility to assess quantitative and morphological data from diseased and non-diseased human lung specimens.Citation Format:
Keywords: thorax; CT; tissue characterization